2016
DOI: 10.1016/j.jaci.2015.12.1327
|View full text |Cite
|
Sign up to set email alerts
|

Peanut T-cell epitope discovery: Ara h 1

Abstract: Preselection of peptides by using in silico and in vitro approaches in combination with conventional methods appears to be an effective strategy for identifying peanut T-cell peptide vaccine candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
0
43
1
Order By: Relevance
“…Indeed, contrasting theoretical information about epitopes prediction and available experimental results (IEDB http://www.iedb.org), for allergens analysed in the current study showed that e.g. all predicted specific epitopes for Ara h 1 ( Figure 4) have been confirmed experimentally and identified as allergens ID 99142, 98985, 98887, 99364 [42][43][44], and 148649, 148770 [43,44]. Searching Lup an 1 specific epitopes (Table 1) in the Ara h 1 epitopes database IEDB allowed us to identify one experimentally confirmed epitope from Ara h 1 (ID 148579) [45,46] that matched with the Lup an 1 epitope VRRYSARLS in 7 out of 9 positions (∼78%), which may be enough to induce cross-reactivity between both proteins.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Indeed, contrasting theoretical information about epitopes prediction and available experimental results (IEDB http://www.iedb.org), for allergens analysed in the current study showed that e.g. all predicted specific epitopes for Ara h 1 ( Figure 4) have been confirmed experimentally and identified as allergens ID 99142, 98985, 98887, 99364 [42][43][44], and 148649, 148770 [43,44]. Searching Lup an 1 specific epitopes (Table 1) in the Ara h 1 epitopes database IEDB allowed us to identify one experimentally confirmed epitope from Ara h 1 (ID 148579) [45,46] that matched with the Lup an 1 epitope VRRYSARLS in 7 out of 9 positions (∼78%), which may be enough to induce cross-reactivity between both proteins.…”
Section: Discussioncontrasting
confidence: 76%
“…Epitopes located in the globular region of Lup an 1 are the ones commonly shared to other legume proteins. In this regard, a large number of epitopes (thirty-six peptides) have been also identified for the peanut allergen Ara h 1 as T-cell epitopes vaccines candidates by using in silico predictions and MHC class II binding assays [44]. Several of these epitopes may be involved in cross-reactivity between Ara h 1 and Lup an 1 [44].…”
Section: Discussionmentioning
confidence: 99%
“…To date, 27 linear epitopes have been recognized within the molecule of Ara h 1, of which the two most potent epitopes are found within the amino acid residues 139 to 147 and 175 to 183 (Matsuo, Yokooji, & Taogoshi, ). Recently, 36 T‐cell epitopes of Ara h 1 have been identified (Ramesh et al., ), which is useful as T‐cell epitopes may play a significant role in development of immunotherapy treatments (Tao et al., ). This information can help the food processing scientists to study the alteration in IgE binding epitopes to lower adverse events yet maintain T‐cell epitopes for immunotherapy purposes.…”
Section: Molecular Characteristics Of Peanut Allergensmentioning
confidence: 99%
“…91 However, because of the increase in food allergies, attention has largely shifted away from epitope mapping of inhalant allergens to focus on food allergens that pose a serious risk of anaphylaxis. 9297 Unfortunately, little is known about the relationship between T-cell epitopes of food allergens and asthma development, although this aspect is worth exploring, particularly among polysensitized children. As of 2010, only approximately 17% of all allergens listed by the International Union of Immunological Societies database had been mapped, indicating much work remains to be done.…”
Section: Tslpmentioning
confidence: 99%